Design rule for improved open-circuit voltage in binary and ternary organic solar cells - Felekidis, Nikolaos; Melianas, Armantas; Kemerink, Martijn (ACS applied materials & interfaces, 2017)
Mixing different compounds to improve functionality is one of the pillars of the organic electronics field. Here, the degree to which the charge transport properties of the constituent materials are simply additive when materials are mixed is quantified. It is demonstrated that in bulk heterojunction organic solar cells, hole mobility in the donor phase depends critically on the choice of the acceptor material, which may alter the energetic disorder of the donor. The same holds for electron mobility and disorder in the acceptor. The associated mobility differences can exceed an order of magnitude compared to pristine materials. Quantifying these effects by a state-filling model for the open-circuit voltage (VOC) of ternary Donor:Acceptor1:Acceptor2 (D:A1:A2) organic solar cells leads to a physically transparent description of the surprising, nearly linear tunability of the VOC with the A1:A2 weight ratio. It is predicted that in binary OPV systems, suitably chosen donor and acceptor materials can improve the device power conversion efficiency (PCE) by several percentage points, for example from 11 to 13.5% for a hypothetical state-of-the-art organic solar cell, highlighting the importance of this design rule.
Gesehen am 27.11.2019